Intrahypothalamic Estradiol Regulates Glucose Metabolism via the Sympathetic Nervous System in Female Rats - Liu, Ji (American Diabetes Association, 2013)
Long-term reduced hypothalamic estrogen signaling leads to increased food intake and decreased locomotor activity and energy expenditure, and ultimately results in obesity and insulin resistance. In the current study, we aimed to determine the acute obesity-independent effects of hypothalamic estrogen signaling on glucose metabolism. We studied endogenous glucose production (EGP) and insulin sensitivity during selective modulation of systemic or intrahypothalamic estradiol (E2) signaling in rats 1 week after ovariectomy (OVX). OVX caused a 17% decrease in plasma glucose, which was completely restored by systemic E2. Likewise, the administration of E2 by microdialysis, either in the hypothalamic paraventricular nucleus (PVN) or in the ventromedial nucleus (VMH), restored plasma glucose. The infusion of an E2 antagonist via reverse microdialysis into the PVN or VMH attenuated the effect of systemic E2 on plasma glucose. Furthermore, E2 administration in the VMH, but not in the PVN, increased EGP and induced hepatic insulin resistance. E2 administration in both the PVN and the VMH resulted in peripheral insulin resistance. Finally, sympathetic, but not parasympathetic, hepatic denervation blunted the effect of E2 in the VMH on both EGP and hepatic insulin sensitivity. In conclusion, intrahypothalamic estrogen regulates peripheral and hepatic insulin sensitivity via sympathetic signaling to the liver.